Translational cultural adaptation and psychometric study of the Persian version of pediatric inventory for parents - Sedigheh Khanjari; Fereshteh Javaheri Tehrani; Shabnam Shariat Panahi; Ahmad Saidee (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Cancer, as a life-threatening disease in children, poses several challenges for parents. It is necessary to have a tool that can comprehensively examine the stressful events for parents of children with cancer. The aim this present study was done with the aim of study the Persian version of pediatric inventory for parents (PIP). MATERIALS AND METHODS: The study was a conducted based on methodological research design. Four hundred and fifteen parents of children with cancer referring to Alia Asghar Children's Hospital and Children's Medical Centre in Tehran answered the Persian version of PIP questionnaire in 2019. a confirmatory factor analysis was carried out using LISREL (software version 8.8) to test the construct validity of PIP. The two tools of parental stress scale and state-trait anxiety inventory (STAI-Y) were used for concurrent validity purposes. RESULTS: The results showed that, the overall score of the questionnaire was higher than the average and related to emotional distress. The internal correlation coefficient (Cronbach's alpha) in both parts of the PIP was between 0.808 and 0.957 and acceptable. Concurrent validity analysis indicated positive and significant correlation of this tool in the difficulty section of the scale with both Parental Stress Scale and STAI-Y. The results of confirmatory factor analysis indicated that the factor loads of all items except three items in the frequency section were more than 0.3 and were appropriate. CONCLUSION: The Persian version of PIP can be available to health and family experts as a valid and reliable tool to assess stressful events of parents of children with cancer.